Control of Plant Trichome and Root-Hair Development by a Tomato (Solanum lycopersicum) R3 MYB Transcription Factor - Tominaga-Wada, Rumi (Public Library of Science, 2013)
In Arabidopsis thaliana the CPC-like MYB transcription factors [CAPRICE (CPC), TRIPTYCHON (TRY), ENHANCER OF TRY AND CPC 1, 2, 3/CPC-LIKE MYB 3 (ETC1, ETC2, ETC3/CPL3), TRICHOMELESS 1, 2/CPC-LIKE MYB 4 (TCL1, TCL2/CPL4)] and the bHLH transcription factors [GLABRA3 (GL3) and ENHANCER OF GLABRA 3 (EGL3)] are central regulators of trichome and root-hair development. We identified TRY and GL3 homologous genes from the tomato genome and named them SlTRY and SlGL3, respectively. Phylogenic analyses revealed a close relationship between the tomato and Arabidopsis genes. Real-time reverse transcription PCR analyses showed that SlTRY and SlGL3 were predominantly expressed in aerial parts of developing tomato. After transformation into Arabidopsis, CPC::SlTRY inhibited trichome formation and enhanced root-hair differentiation by strongly repressing GL2 expression. On the other hand, GL3::SlGL3 transformation did not show any obvious effect on trichome or non-hair cell differentiation. These results suggest that tomato and Arabidopsis partially use similar transcription factors for epidermal cell differentiation, and that a CPC-like R3 MYB may be a key common regulator of plant trichome and root-hair development.